PELATIHAN DESAIN UI/UX APLIKASI ANDROID PADA SMK TRITECH INFORMATIKA MEDAN - Fetty Ade Putri; Rahman, Maulia; Aditya, Wahyu (LPPM Universitas Potensi Utama, 2023)
UI/UX design is a design from the pre-product stage before being implemented into a desired product. In this pre-production phase, the UI/UX design is often not implemented by the developers of software tools and applications, so it sometimes creates objections to users about product implementation that are not given much attention. One of the professional needs to support the learning process for students is to attend training. The knowledge and skills of students especially RPL majoring in UI and UX design are still relatively low, so they need to be provided with UI/UX training in the form of mobile applications. In this community service, a training on UI/UX design in making android applications is carried out for students of SMK Tritech Informatika, especially software engineering majors, as a basic preparation for students to be more interested in taking majors related to design and applications. The results of this community service are that the delivery of UI / UX material is well implemented and the examples that are practiced are in accordance with the daily needs of the community so that they can produce applications that can compete in the business and industrial world.